2012
DOI: 10.1007/s10661-012-2628-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of eutrophication on the occurrence of Trichodesmium in the Cochin backwaters, the largest estuary along the west coast of India

Abstract: Phytoplankton studies in early 1970s have shown the annual dominance of diatoms and a seasonal abundance of Trichodesmium in the lower reaches of the Cochin backwaters (CBW) and adjacent coastal Arabian Sea during the pre-summer monsoon period (February to May). Surprisingly, more recent literature shows a complete absence of Trichodesmium in the CBW after 1975 even though their seasonal occurrence in the adjacent coastal Arabian Sea continued without much change. In order to understand this important ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 30 publications
1
2
1
Order By: Relevance
“…Similar assumptions have been quoted [37,69]. Moreover, nutrient fortification is a frequent syndrome observed in the Cochin estuary [41,43,44] which eventually enhances algal population leading to lowering of TOC:TN values [24,34,56]. Thus, the organic matter summation in Cochin estuary is profoundly under the influence of amalgamation of marine, terrestrial and sewage inputs.…”
Section: Discussionsupporting
confidence: 62%
“…Similar assumptions have been quoted [37,69]. Moreover, nutrient fortification is a frequent syndrome observed in the Cochin estuary [41,43,44] which eventually enhances algal population leading to lowering of TOC:TN values [24,34,56]. Thus, the organic matter summation in Cochin estuary is profoundly under the influence of amalgamation of marine, terrestrial and sewage inputs.…”
Section: Discussionsupporting
confidence: 62%
“…The long whitish bands of Trichodesmium bloom evident in Fig. 6, differed from the routine thick yellowish band reported earlier (Jyothibabu et al, 2003;Martin et al, 2013;Mohanty et al, 2010), indicated the late stage of the bloom decomposition.…”
Section: Chlorophyll a Primary Production And Trichodesmium Bloomcontrasting
confidence: 58%
“…It is experimentally proved that Trichodesmium can assimilate nutrients such as NO 3 , NH 4 and PO 4 (Holl and Montoya, 2005;Lin et al, 1998;Martin et al, 2013;Ohki et al, 1986;Stihl et al, 2001). Paradoxically, when the nutrients exist in high concentrations, they inhibit the growth of Trichodesmium (Holl and Montoya, 2005;Lin et al, 1998;Martin et al, 2013;Ohki et al, 1986;Stihl et al, 2001).…”
Section: Trichodesmium Bloom and Warm Core Eddymentioning
confidence: 99%
See 1 more Smart Citation